Heavy Water as a Probe of the Free Radical Nature and Electrical Conductivity of Melanin - Paul Meredith (The Journal of Physical Chemistry B, 2015)
Melanins are pigmentary macromolecules found in many locations throughout nature including plants and vertebrate animals. It was recently proposed that the predominant brown-black pigment eumelanin is a mixed ionic–electronic conductor which has led to renewed interest in its basic properties as a model bioelectronic material. This exotic hybrid electrical behavior is strongly dependent upon hydration and is closely related to the free radical content of melanin which is believed to be a mixed population of two species: the semiquinone (SQ) and a carbon-centered radical (CCR). The predominant charge carrier is the proton that is released during the formation of the SQ radical and controlled by a comproportionation equilibrium reaction. In this paper we present a combined solid-state electron paramagnetic resonance (EPR), adsorption, and hydrated conductivity study using D2O as a probe. We make specific predictions as to how the heavy isotope effect, in contrast to H2O, should perturb the comproportionation equilibrium and the related outcome as far as the electrical conductivity is concerned. Our EPR results confirm the proposed two-spin mechanism and clearly demonstrate the power of combining macroscopic measurements with observations from mesoscopic probes for the study of bioelectronic materials.